Pharmacological Effects of Benzimidazole Derivatives (International Journal of Scientific Research in Science and Technology, 2025)
In the field of Medicinal Chemistry, the uses of heterocyclic compounds increased day by day, because in many biological materials, heterocyclic compound is a part of its structure. Benzimidazole is a heterocyclic compound which formed by fusion of benzene and imidazole. Benzimidazole contains two nitrogen’s as heteroatom. Benzimidazole derivatives are more effective, medicinally useful compounds and extensive biochemicals. Derivatives of benzimidazole have found practical applications in various fields. These nitrogen-containing bicyclic structures are structural analogs of purines and have been extensively studied due to their diverse biological activities, including antifungal, antidiabetic, antiviral, anticancer, anti-inflammatory, and antimicrobial effects. This paper is summarized to know about the chemistry of different derivatives of substituted benzimidazoles along with their pharmacological activities. The molecular versatility of benzimidazole allows for functional modifications that enhance bioavailability and potency, making it a valuable scaffold in medicinal chemistry.
Keywords: Heterocycle; Benzimidazole; Pharmacological Activities; Drug Design